Chronic cutaneous chest wall fistula and gallstone empyema due to retained gallstones. (14th August 2014) - Gaster, Richard S; Berger, Aaron J; Ahmadi-Kashani, Mastaneh; Shrager, Joseph B; Lee, Gordon K
Abstract : We report a case of a 72-year-old man who presented with a persistent pleural effusion and painful abscess in the right lower chest wall 6 months following a laparoscopic cholecystectomy. The patient subsequently developed a chronic cutaneous chest wall fistula requiring a large resection and complex closure. The complication was likely secondary to intraoperative spillage of gallstones. While previous reports describe gallstone spillage in the abdominal cavity as benign, this case illustrates that stones left in the abdominal cavity can potentially lead to significant morbidity. Therefore, stones should be diligently removed from the abdominal cavity when spillage occurs. In addition, it is important that operative notes reflect the occurrence of stone spillage so stones may be suspected when a patient presents with an abdominal or thoracic infection following a cholecystectomy.